Exploration of Physics Concepts in the Process of Making the Siwalan Dawet Ice: Does it Have the Potential as a Source of Physics Learning in the Independent Learning Curriculum? - Rusmaya, Anggita; A'yun, Septy Kurrota; Suprapto, Nadi; Admoko, Setyo (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
The siwalan dawet ice is a form of local wisdom that contains rich physics concepts and has potential applications in physics learning. To date, there has been no study that explicitly explores the physics concepts embedded in this local wisdom. Therefore, this study aims to identify and analyze the physics concepts involved in the process of making the siwalan dawet ice. This study employed a qualitative descriptive method through an analytical approach. Data were collected using three techniques: literature review, observation, and interviews, and were subsequently triangulated to enhance the validity of the findings. Qualitative data analysis was conducted through data reduction, data display, and conclusion drawing. The results reveal that the process of making the siwalan dawet ice involves several physics concepts, including hydrostatic pressure, Pascal’s Law, Archimedes’ Law, density, and temperature and heat. These findings indicate that the siwalan dawet ice has strong potential to be integrated into physics learning within the Merdeka Curriculum as a local wisdom–based learning resource that supports contextual and meaningful learning. This study implies that incorporating local cultural practices into physics instruction can provide concrete learning experiences, enhance student engagement, and serve as an alternative approach to facilitating students’ understanding of abstract physics concepts. Further research is recommended to examine the effectiveness of this learning resource in improving students’ motivation and learning outcomes.